Frequency of mutations in PROP-1 gene in Turkish children with combined pituitary hormone deficiency - Kandemir, Nurgün; Vurallı, Doğuş; Taşkıran, Ekim; Gönç, Nazlı; Özön, Alev; Alikaşifoğlu, Ayfer; Yılmaz, Engin (The Turkish Journal of Pediatrics, 2012)
Mutations in the prophet of Pit-1 (PROP-1) gene are responsible for most of the cases of combined pituitary hormone deficiencies (CPHD). We performed this study to determine the prevalence of PROP-1 mutations in a group of Turkish children with CPHD. Fifty-three children with the diagnosis of CPHD were included in this study. Clinical data were obtained from medical files, and hormonal evaluation and genetic screening for PROP-1 mutations were performed. A homozygous S109X mutation was found in the second exon in two brothers, and they had growth hormone (GH) and thyroid-stimulating hormone (TSH) deficiencies and normal prolactin levels. In the third exon of the PROP-1 gene, a heterozygous A142T polymorphism was found in 14 patients and a homozygous A142T polymorphism was found in 3 patients. In the first exon, a homozygous A9A polymorphism was found in 7 patients and a heterozygous A9A polymorphism was found in 31 patients. We assumed that mutations in the PROP-1 gene in cases with CPHD were expected to be more prevalent in our population due to consanguinity, but it was found that these mutations were far less than expected and that it was rare in non-familial cases.